In-vitro comparative thermo-chemical aging and penetration analyses of bioactive glass-based dental resin infiltrates - Syed Zubairuddin Ahmed; Abdul Samad Khan; Maram Alshehri; Fatimah Alsebaa; Fadak Almutawah; Moayad Mohammed Aljeshi; Asma Tufail Shah; Budi Aslinie Md Sabri; Sultan Akhtar; Mohamed Ibrahim Abu Hassan (PeerJ)
Background Teeth with small to moderate cavities can be repaired with enamel resin infiltrants, a form of dental restorative material. In dental materials, it is standard practice to include several filler particles for experimental use in dental resin infiltrates. The resin’s BG particles penetrate the lesion and release ions that combine with saliva to provide a mineral-rich environment that can strengthen enamel and heal. This study aimed to compare resin infiltrants based on three types of bioactive glass materials and investigate the penetration depth, microleakage, and the effect of thermal and chemical aging. Methodology A triethylene glycol dimethacrylate (TEGDMA) and urethane dimethacrylate (UDMA)-based experimental resin infiltrate was prepared. Initial mixing was done manually for 1 h at room temperature, followed by another mix for 30 min on a magnetic stirrer. This prepared resin, called “PURE RESIN” was then further incorporated with three different types of bioactive glasses, i.e., Bioglass (45S5), boron-substituted (B-BG), and fluoride-substituted (F-BG). Initial manual mixing for 1 h, followed by ultrasonic mixing for 3 min and then proceeded for the final mixing on a magnetic stirrer for 24 h in a dark room at ambient temperature. Human-extracted teeth were demineralized, and the experimental resins were infiltrated on the demineralized surface. The surface area, pore size, and volume of the demineralized surface were measured. The microleakage and penetration depth were analyzed with the stereomicroscope and micro-CT, respectively. The samples were challenged with the pH cycle for 14 days, followed by a scanning electron microscope (SEM). Thermocycling (5,000 cycles) and chemical aging (4 weeks) were conducted, followed by microhardness, surface roughness, and SEM analyses. Statistical analyses were conducted after each test. Results The F-BG group achieved the highest initial and day 14 penetration coefficients. There was a superior dye penetration with the microleakage analysis in the F-BG group. The 45S5 group had the highest average penetration depth via micro-CT analysis. After thermocycling and chemical aging, the micro-hardness was reduced (non-significantly) among all samples except the F-BG group in post-chemical aging analysis, whereas the surface roughness was significantly increased. SEM images showed the presence of micro-pits on the surfaces after the thermal and chemical aging. Conclusion The F-BG group achieved the highest initial and day 14 penetration coefficients. There was a superior dye penetration with the microleakage analysis in the F-BG group. The 45S5 group had the highest average penetration depth via micro-CT analysis. After thermocycling and chemical aging, the micro-hardness was reduced (non-significantly) among all samples except the F-BG group in post-chemical aging analysis, whereas the surface roughness was significantly increased. SEM images showed the presence of micro-pits on the surfaces after the thermal and chemical aging.